The risks of oxygen therapy - Sosan Ovaisi (Iran University of Medical Sciences, 1993)
Although delivering of oxygen to patients seems to be easy, but this procedure can include some risks. In this article, we try to show you how this procedure can perform in a safe manner.   Have you ever worked in a medical-surgical ward, or emergency department, or also in intensive care unit?   Perhaps you ever have the care of patients who have need for supplemental oxygen. Oxygen therapy is effective in order to increase blood oxygen and provide sufficient oxygen to patients' tissues. This oxygen can decrease the additional load on patients' heart and lung. However, using of supplemental oxygen does not capable to correct underlining cause of oxygen deficiency.